Utilizing DeepFace for Emotion Detection to Enhance User Experience in a School Library Application - Hasibuan, Rizqy Sultan Pujangga; Purwawijaya, Ellanda; Rambe, Aripin (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
The library is an essential facility that supports teaching and learning activities in schools. However, the library at SMP Pertiwi Medan still uses a manual system for book loan administration and has experienced a decline in students’ interest in visiting the library for reading. This study aims to design and develop a digital-based library application integrated with a visitor comfort detection system using the DeepFace method on a desktop platform. The application not only provides efficient features for managing book data, borrowing, and returning, but also measures visitors’ nonverbal comfort levels while they are in the library. This measurement aims to obtain data that can serve as a basis for evaluating comfort levels and designing strategies to increase students’ reading interest. The implementation of this application is expected to improve the efficiency of library management and provide a solution to enhance the quality of service as well as the attractiveness of the library for students.